HUBUNGAN ANTARA KEPATUHAN PENGGUNAAN MASKER DENGAN KEJADIAN COVID-19 DI KELURAHAN BENGKOL KECAMATAN MAPANGET KOTA MANADO - Nancy Sampouw (Fakultas Keperawatan, Universitas Klabat, 2022)
Introduction: Coronavirus Disease 2019 or abbreviated as COVID-19 is a new infectious disease in humans caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-1). COVID-19 infection shows the main symptom in the form of acute respiratory distress. One ofe the prevention and mitigation effort to suppress the transmission of COVID-19 infection is to use a mask. The purpose of the study was to determine the relationship between adherence to the use of masks and the incidence of COVID-19 in Bengkol Village, Mapanget District, Manado City. Methods: The quantitative research method uses a correlational design with a cross sectional approach. The sample used was 61 people who were confirmed positive for COVID-19 using the total sapling technique. The process of collecting data using a questionnaire and statistically tested with the percentage formula to answer the first and second statements, the Chi-Square Correlation test to answer the third statement. Result: The description of compliance with the use of masks is the high category of 75 respondents (83%), the description of the incidence of COVID-19 is the reactive or positive category as many as 61 respondents (68%), based on the results of the Chi-Square test, the significance of which is 0.563 (p > 0.05), then H0 accepted. Conclusion: There is no relationship between adhrerence to the use of masks and the incidence of COVID-19 in Bengkol Village, Mapanget District, Manado City. It was found that most respondents always use masks but there are still many who are infected with COVID-19, this can be caused by other factors that can cause COVID-19 infection, namely not complying with other health protocols, namely washing hands and maintaining distance.It is recommended for the future researchers to use a retrospective cohort study design. KEYWORDS: Compliance With the Use of Masks, COVID-19 Pendahuluan: Coronavirus Disease 2019 atau disingkat dengan COVID-19 adalah penyakit infeksi baru pada manusia disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Infeksi COVID-19 menunjukkan gejala utama yaitu berupa gangguan pernapasan akut. Salah satu upaya pencegahan dan mitigasi untuk menekan penularan infeksi COVID-19 yaitu dengan menggunakan masker. Tujuan penelitian yaitu untuk mengetahui hubungan antara kepatuhan penggunaan masker dengan kejadian COVID-19 di Kelurahan Bengkol Kecamatan Mapanget Kota Manado. Metode: Metode penelitian kuantitatif menggunakan desain koreslasional dengan pendekatan cross sectional. Sampel yang digunakan sebanyak 90 responden dengan menggunakan teknik total sampling. Proses pengumpulan data menggunakan kuesioner dan diuji statistik dengan rumus presentase untuk menjawab pernyataan pertama dan kedua, uji hubungan Chi-Square untuk menjawab pernyataan ketiga. Hasil: Gambaran kepatuhan penggunaan masker yaitu kategori tinggi sebanyak 75 responden (83%), gambaran kejadian COVID-19 yaitu kategori reaktif atau positif sebanyak 61 responden (68%), berdasarkan hasil uji Chi-Square signifikansi sebesar 0,563 (p > 0,05) maka H0 diterima. Kesimpulan: Tidak ada hubungan antara kepatuhan penggunaan masker dengan kejadian COVID-19 di Kelurahan Bengkol Kecamatan Mapanget Kota Manado. Didapati sebagian besar responden selalu menggunakan masker tapi masih banyak yang terinfeksi COVID-19, hal ini dapat disebabkan karena terdapat faktor lain yang dapat menyebabkan terinfeksi COVID-19 yaitu kurang patuh terhadap protokol kesehatan lainnya yaitu mencuci tangan dan menjaga jarak. Direkomendasikan bagi peneliti selanjutnya untuk dapat menggunakan desain penelitian kohort retrospektif. KATA KUNCI: COVID-19, Kepatuhan Penggunaan Masker.